2023
DOI: 10.1021/acs.jmedchem.2c01523
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of Targeting CK2 in Drug Discovery: Challenges, Opportunities, and Emerging Prospects

Abstract: CK2 (casein kinase 2) is a serine/threonine protein kinase that is ubiquitous in eukaryotic cells and plays important roles in a variety of cellular functions, including cell growth, apoptosis, circadian rhythms, DNA damage repair, transcription, and translation. CK2 is involved in cancer pathogenesis and the occurrence of many diseases. Therefore, targeting CK2 is a promising therapeutic strategy. Although many CK2specific small-molecule inhibitors have been developed, only CX-4945 has progressed to clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 199 publications
(400 reference statements)
0
12
0
Order By: Relevance
“…Considering that natural compounds have remained an important avenue for drug discovery, the recently published PIM inhibitors based on natural products also warrant attention. For these small molecule inhibitors, particular emphasis has been placed on optimization strategies, structure–activity relationships (SARs), and the potency of inhibiting PIM kinases. …”
Section: Introductionmentioning
confidence: 99%
“…Considering that natural compounds have remained an important avenue for drug discovery, the recently published PIM inhibitors based on natural products also warrant attention. For these small molecule inhibitors, particular emphasis has been placed on optimization strategies, structure–activity relationships (SARs), and the potency of inhibiting PIM kinases. …”
Section: Introductionmentioning
confidence: 99%
“…Protein kinase CK2 (CK2) is involved in various important cellular functions, including signal transduction and gene expression. [1][2][3][4][5][6] CK2 functions as a hetero-tetrameric holoenzyme comprising two catalytic subunits (CK2α and/or CK2α′) and two identical regulatory subunits (CK2β). 7 CK2 is also known to be associated with the progression of glomerulonephritis [8][9][10] neurodegenerative diseases (e.g., Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising that dysregulation of CK2 contributes to the etiology of multiple human diseases, including cancer, neurodegeneration, and even COVID-19 viral infection [4][5][6]. Therefore, CK2 has been the subject of extensive research for the development of effective and selective inhibitors for the treatment of these diseases, with a special focus on cancer treatment [6,7]. However, despite decades of research since the first CK2 inhibitor was identified in 1990, only silmitasertib (CX-4945) has received FDA approval with limited use in clinical trials for some forms of cancer [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been used to develop CK2 inhibitors [7]. These approaches include blocking the substrate channel, disrupting the holoenzyme assembly by interfering with CK2β binding, and targeting putative allosteric sites outside the catalytic box [38][39][40], although the most studied mode of inhibition has been through ATP analogs that compete with ATP to prevent substrate phosphorylation [8,39,[41][42][43].…”
Section: Introductionmentioning
confidence: 99%